La Révolution française a bien eu lieu ! - Jérôme Lamy (Socio, 2016)
In this article we adopt a sociological line of argument to challenge the way in which François Furet constructed a dual discourse on the Terror. Furet defends the idea that the French Revolution-event was the matrix of all insurrections. But, at the same time, he proclaimed his rejection of historiographical determinism. Caught between these two contradictory sets of argumentation, Furet remained a prisoner of his epistemological presentism.